2017
DOI: 10.1097/ccm.0000000000002626
|View full text |Cite
|
Sign up to set email alerts
|

Readmissions for Recurrent Sepsis: New or Relapsed Infection?*

Abstract: Objective Sepsis hospitalizations are frequently followed by hospital readmissions, often for recurrent sepsis. However, it is unclear how often sepsis readmissions are for relapsed/recrudescent versus new infections. The aim of this study was to assess the extent to which 90-day readmissions for recurrent sepsis are due to infection of the same site and same pathogen as the initial episode. Design Retrospective cohort study. Setting University of Michigan Health System. Patients All hospitalizations (Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 36 publications
4
47
0
2
Order By: Relevance
“…Using this information, overall certainty of evidence was assessed as per GRADE system of assessment of evidence about prognosis (see main results) [24] EHR electronic health record, MC multi-centre, SC single-centre Table 2). The relationship between infection at index sepsis admission and the infection diagnosis at rehospitalisation was reported in one study as recurrent or unresolved in nearly 50% of cases [52], often secondary to opportunistic pathogens like Pseudomonas aeruginosa and Candida species in another study [55], and same site as index sepsis admission in 68% of rehospitalisation events in another study [32]. Infection-related rehospitalisation was the most common rehospitalisation event in sepsis survivors.…”
Section: Diagnosis At Rehospitalisationmentioning
confidence: 97%
See 2 more Smart Citations
“…Using this information, overall certainty of evidence was assessed as per GRADE system of assessment of evidence about prognosis (see main results) [24] EHR electronic health record, MC multi-centre, SC single-centre Table 2). The relationship between infection at index sepsis admission and the infection diagnosis at rehospitalisation was reported in one study as recurrent or unresolved in nearly 50% of cases [52], often secondary to opportunistic pathogens like Pseudomonas aeruginosa and Candida species in another study [55], and same site as index sepsis admission in 68% of rehospitalisation events in another study [32]. Infection-related rehospitalisation was the most common rehospitalisation event in sepsis survivors.…”
Section: Diagnosis At Rehospitalisationmentioning
confidence: 97%
“…Similar to all-cause rehospitalisation, the risk factors for infection-related rehospitalisation were older age, prolonged hospitalisation, and nursing home residence [55]. In three studies, infectionrelated rehospitalisation episodes were associated with greater risk of death [32,52,55] when compared to noninfection-related hospitalisations.…”
Section: Independent Risk Factors For All-cause Rehospitalisationmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, infection or sepsis are likely to be the leading causes of readmission in pediatric sepsis survivors, a finding consistent with previous studies in adults. 13 Potential reasons include inadequate duration of antimicrobial therapy (an unrecognized reservoir of infection) and preexisting or persistent immune dysfunction. The latter may be due to epigenetic changes or persistent alterations in the microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…10 Recent work has revealed that sepsis is the leading cause of readmissions in adults, 4 but the epidemiology, causes, and health care spending for readmissions after pediatric sepsis remain poorly understood. In particular, the frequency of readmissions due to infections is of interest because previous studies indicated that immunosuppression, 11 alterations in the microbiome, 12 and partially treated infections 13 may be common among patients with sepsis.…”
mentioning
confidence: 99%